PENGEMBANGAN MODUL MATERI KEANEKARAGAMAN HAYATI UNTUKSMA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION BERBASIS QR CODE - Ari Purnama Sari; Handoko Santoso; Agil Lepiyanto (EDUBIOLOCK, 2023)
The aims of this module development research is to be able to produce aproduct in the form of a module that uses a QR Code-based problem-basedinstruction learning model. This development research uses the 4Ddevelopment type which has 4 stages, namely define, design, develop,dessiminate. Development only does up to the develop stage. The productsdeveloped in this development are modules, the modules have passed the expertdesign validation stage with results of 82.5% with "good" criteria, validation ofmaterial experts with 91.6% results with "very good" criteria, and small grouptrials with 83.3% results with "good" criteria. Based on validation and smallgroup testing, the module is feasible to use in the field.